2020
DOI: 10.3390/nu12103015
|View full text |Cite
|
Sign up to set email alerts
|

Putative Mechanisms Responsible for the Antihyperglycemic Action of Lactobacillus paracasei HII01 in Experimental Type 2 Diabetic Rats

Abstract: Despite the updated knowledge of the impact of gut dysbiosis on diabetes, investigations into the beneficial effects of individual bacteria are still required. This study evaluates the antihyperglycemic efficacy of Lactobacillus paracasei HII01 and its possible mechanisms in diabetic rats. Diabetic rats were assigned to receive vehicle, L. paracasei HII01 (108 CFU/day), metformin 30 (mg/kg) or a combination of L. paracasei HII01 and metformin. Normal rats given vehicle and L. paracasei HII01 were included. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 43 publications
1
17
2
Order By: Relevance
“…In addition, Lactobacillus was more abundant in the gut microbiota of healthy controls and primary hypertension patients than in PA patients. Several studies have already demonstrated that the administration of Lactobacillus could alleviate hyperglycemia in diabetic rats (6,24,25). We also found that Lactococcus and Enterococcus were present in lower abundances in PA patients.…”
Section: Discussionsupporting
confidence: 66%
“…In addition, Lactobacillus was more abundant in the gut microbiota of healthy controls and primary hypertension patients than in PA patients. Several studies have already demonstrated that the administration of Lactobacillus could alleviate hyperglycemia in diabetic rats (6,24,25). We also found that Lactococcus and Enterococcus were present in lower abundances in PA patients.…”
Section: Discussionsupporting
confidence: 66%
“…Although antibacterial effects of metformin are not fully understood, the underlying metabolic mechanisms of metformin are widely attributed to the activation of AMPK [ 65 ]. Toejing et al found that metformin ameliorates endotoxemia and inflammation through the AMPK-NF- κ B pathway [ 31 , 66 ]. Mammalian AMPK is generally thought of as a sensor for adenine nucleotides, activated in a state of low cellular energy.…”
Section: Discussionmentioning
confidence: 99%
“…Another probable pathway mediating the connection between gut microbiota and metabolic endotoxemia is gut permeability [ 4 ]. Our previous study demonstrated that supplementation with the L. paracasei HII01 for 12 weeks in T2DM rat resulted in lessening plasma levels of DX-4000-FITC, suggesting an improvement of gut barrier integrity [ 38 ]. This effect could directly ameliorate systemic endotoxemia by reducing the leakage of LPS into systemic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…These SCFAs are not only of importance in gut health as signaling molecules but might also enter the systemic circulation and directly affect peripheral tissues via AMPK activation and subsequently GLUT4 translocation to membrane for uptake of glucose into cells [ 45 ]. In addition, our previous study found that supplementation of L. paracasei HII01 alleviated hyperglycemia in diabetic rats via increasing glucose uptake by the skeletal muscle which was mediated partly by PI3K/Akt and AMPK activation [ 38 ].…”
Section: Discussionmentioning
confidence: 99%